2017
DOI: 10.3390/su9122358
|View full text |Cite
|
Sign up to set email alerts
|

Improved Precision and Efficiency of a Modified ORG0020 Dynamic Respiration Test Setup for Compost Stability Assessment

Abstract: Abstract:The ORG0020 dynamic respiration test is effective at distinguishing source segregated organic waste derived composts across a wide range of stabilities when compared to other standard tests; however, using the original diaphragm pump and manifold setup, the test is affected by variability in flow rate with time and across sample replicate vessels. Here, we demonstrate the use of a multichannel peristaltic pump to deliver a more consistent air flow to individual vessels. Using finished and unfinished i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The flow rate and flow configuration have been found to be important factors within respirometry testing [30][31][32]. Guillen Ferrari et al [33] found that optimising the aeration within the ORG0020 test improved precision within the setup. An airflow configuration that was purely within the headspace of a chamber, as used in ORG0020, may work reliably especially with more stable materials, and may be considered more realistically representative of the exchange of air over a tray or pot within a glasshouse.…”
Section: Respirometrymentioning
confidence: 99%
“…The flow rate and flow configuration have been found to be important factors within respirometry testing [30][31][32]. Guillen Ferrari et al [33] found that optimising the aeration within the ORG0020 test improved precision within the setup. An airflow configuration that was purely within the headspace of a chamber, as used in ORG0020, may work reliably especially with more stable materials, and may be considered more realistically representative of the exchange of air over a tray or pot within a glasshouse.…”
Section: Respirometrymentioning
confidence: 99%